2021
DOI: 10.3390/ijms22168659
|View full text |Cite
|
Sign up to set email alerts
|

Single Dose of N-Acetylcysteine in Local Anesthesia Increases Expression of HIF1α, MAPK1, TGFβ1 and Growth Factors in Rat Wound Healing

Abstract: In this study, we aimed to investigate the influence of N-acetylcysteine (NAC) on the gene expression profile, neoangiogenesis, neutrophils and macrophages in a rat model of incisional wounds. Before creating wounds on the backs of 24 Sprague–Dawley rats, intradermal injections were made. Lidocaine–epinephrin solutions were supplemented with 0.015%, 0.03% or 0.045% solutions of NAC, or nothing (control group). Scars were harvested on the 3rd, 7th, 14th and 60th day post-surgery. We performed immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 103 publications
(131 reference statements)
2
6
5
Order By: Relevance
“…This may lead to the potential exacerbation of the wound. This contradicts our previously published findings [9], which showed that a single dose of NAC at any concentration had no significant impact on any of the assessed histological categories at the same time points. This further supports the claim of the superiority of a single dose of NAC over multiple doses.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This may lead to the potential exacerbation of the wound. This contradicts our previously published findings [9], which showed that a single dose of NAC at any concentration had no significant impact on any of the assessed histological categories at the same time points. This further supports the claim of the superiority of a single dose of NAC over multiple doses.…”
Section: Discussioncontrasting
confidence: 99%
“…Promising effects and a lack of substantial side effects encouraged us to explore whether an extension of the therapy from pre-incision to the early phase of wound healing may turn out to be even more fruitful. Recently, we showed that a single dose of NAC applied after the creation of a wound produced slightly slimmer scars with improved histology [9] followed by long-term (over a 60 day observation period) shifts in the gene expression of crucial targets for wound healing and remodeling [10]. Notably, the HIF1alpha pathway was pronouncedly expressed at all timepoints, which is consistent with the findings of other authors, and may be the basis of NAC efficiency in improving wound healing [11,12].…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Progressive fibrosis during wound healing causes scarring, characterized by excessive extracellular matrix deposition and overexpression of fibrosis-related genes. Paskal et al 50 revealed that NAC dysregulated the expressions of numerous genes associated with scar formation and improved neovascularization. The present study revealed that NAC significantly downregulated the expression of mRNA for fibrosis-related genes ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%